STRATEGI PEMASARAN PAKET WISATA PILGRIM PT. DONGAN SAHUTA TOUR AND TRAVEL DI BALI - Putri Amelia, Paradita; Oka Karini, Ni Made; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017), 2017)
This study aimed to determine the marketing activities of pilgrim package tour that have been performed by PT. Dongan Sahuta Tour and Travel, develop strategies and also marketing programs that can be implemented by the company. Data collection by observation, interviews, questionnaires and literature study. The sampling technique used purposive sampling. Data were analyzed using qualitative descriptive analysis, analysis of the Likert scale and SWOT analysis approach. The results obtained there are four teen indicators of strengths, weaknesses of tree indicators, four indicators of opportunities and four indicators threats. Marketing strategies that can be implemented by the firm such as 1)create and develop a quality product, 2)provide rebates to customers who have used the services of PT. Dongan Sahuta Tour and Travel several times.The advice given are more active in the promotion by giving rebates, conduct marketing activities as E-commers, expand cooperation with business trips or individuals.
Keywords: Marketing Environment, Marketing Strategy, Pilgrim Package